Pediatric Diffuse Midline Gliomas H3 K27M-Mutant and Non-Histone Mutant Midline High-Grade Gliomas in Neurofibromatosis Type 1 in Comparison With Non-Syndromic Children: A Single-Center Pilot Study - Garibotto, Federica; Madia, Francesca; Milanaccio, Claudia; Verrico, Antonio; Piccardo, Arnoldo; Tortora, Domenico; Piatelli, Gianluca; Diana, Maria Cristina; Capra, Valeria; Garrè, Maria Luisa; Rossi, Andrea; Morana, Giovanni (Frontiers in Oncology, 2020)
Background: Pediatric neurofibromatosis type 1 (NF1) patients rarely develop aggressive central nervous system tumors. Among high-grade gliomas (HGGs), histone mutant diffuse midline gliomas (DMGs H3 K27M-mutant) have exceptionally been reported. The aim of this retrospectives single-center study was to compare the clinical behavior of DMGs H3 K27M-mutant and non-histone mutant midline HGGs in NF1 vs. non-syndromic children and to report imaging features of NF1 HGGs. Method: We conducted a retrospective review of cerebral DMGs H3 K27M-mutant or non-histone mutant HGGs in 18 patients with or without NF1 followed at our institution between 2010 and 2018. Differences in outcomes, notably progression-free survival (PFS) and overall survival (OS), were evaluated. Results: Two patients were identified with genetically confirmed diagnosis of NF1 and cerebral HGGs (one DMG H3 K27M-mutant and one histone wild type). Both subjects presented with midline mass lesions with imaging features of aggressive biological activity on advanced MRI or amino-acid PET. During the same time period, 16 non-NF1 patients (11 subjects with DMGs H3 K27M-mutant and 5 with non-histone mutant midline HGGs) were treated at our institution. The two patients with NF1 and HGGs presented a PFS of 3 months and an OS of 5 and 7 months. Median PFS and OS of children without NF1 were respectively 6 and 10 months in DMGs H3 K27M-mutant, and 6 and 11 months in H3 K27M wild-type tumors. Seventy-five percent of subjects with non-NF1 HGGs presented a PFS >4 months compared to 0% in NF1 patients. The 8-month OS of patients with non-NF1 HGGs was 81% compared to 0% in NF1 patients. Conclusions: Cerebral HGGs arising in midline structures rarely occur in pediatric patients with NF1 and present with extremely poor prognosis, worse than HGGs developing in non-NF1 patients, independent of the presence or absence of H3 K27M mutation. Imaging features of aggressive biological activity on advanced MRI or amino-acid PET imaging suggest prompt neuropathological and molecular investigations.